A purple plaque in a patient with systemic sclerosis. Issue 2 (June 2023) - Ramyead, Sheena; Denton, Christopher P; Orteu, Catherine H; Swale, Victoria; Mayor-Jerez, Jorge; Gardette, Emma
We present the case of a 43-year old woman with anti-U3 ribonucleoprotein antibody-positive systemic sclerosis presenting with an enlarging purple plaque on the left upper arm. The skin was not sclerotic; however, there had been a cluster of long-standing telangiectases preceding the plaque. Histology and immunohistochemistry confirmed an angiosarcoma. There are five reported cases in the literature about angiosarcoma arising in the skin of patients with systemic sclerosis; however, to our knowledge, this is the first to have arisen from non-sclerotic skin. We would urge clinicians to adopt a high index of suspicion for atypical vascular tumours presenting in patients with systemic sclerosis.